The Effectiveness of the Expansions Method in Improving Mean Length of Utterance (MLU) in Children with Communication Disorders - Luthfiyyah Harmi; Anggi Resina Putri; Gunawan Gunawan (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
One of the problems experienced by children with communication disorders is language disorders. An important indicator in a child's language development is Mean length of utterance (MLU), which measures the average length of a child's utterances. There are various techniques or methods that can be used to increase the length of utterances, including the expansions method. This study aims to examine the effectiveness of the expansions method in improving MLU in children with communication disorders at SLBN Surakarta. This is a quantitative study with an experimental research design using a one-group pre-test post-test, involving 8 students (n=8) with 8 treatments and data analysis using the Shapiro-Wilk normality test and the Paired T-Test statistical test. A p-value (sig.) of 0.013 (p < 0.05) was obtained, indicating a significant difference between MLU scores before and after the application of the expansions method. Thus, the results of this study indicate that the application of theexpansions method has the potential to positively influence MLU improvement in children with communication disorders at SLBN Surakarta.